Exploring government and civil society workers' perceptions of urban health as a governance priority in the Lagos metropolis. Issue 2 (6th April 2018) - Mogo, Ebele; Litt, Jill; Leiferman, Jenn; McManus, Beth; Risendal, Betsy; Oshodi, Lookman
Abstract: While cities may have compelling agendas for urban health, it is necessary for that vision to be translated into the work of their ministries and local governments. We qualitatively explored how workers in the urban service delivery sectors understood their priorities and the place of health in their agenda. Based on the interviews, we propose the following priorities for research and investments in urban development in Lagos: (1) low cost, climate friendly, health friendly, scalable solutions to the pressing problems of housing, pollution, land, waste management and health (2) legal, financial and political pressure to ensure that public private partnerships are framed around health, equity and the environment (3) critique international donor agendas to see if they are centred in the Sustainable Development Goal principles of equity, particularly for the urban poor (4) test behavioural tools for changing public attitudes to environmental health (5) integrated knowledge translation initiatives around the integration of public health concerns in urban policy (6) train decision-makers to see urban development issues through a human rights, equity and health lens. While every city is different, we hope these lessons will inspire similar research efforts across other African cities.